Effect and Mechanism of Transthyretin Over-Expression on Pro-liferation and Cell Cycle of Lung Cancer A549 Cells - Deqing Zhu; Xuan Li; Hao Gong; Jing Li; Xike Lu; Honggang Xia; Xia Chen; Lan Ma; Zhongyi Sun; Xun Zhang; Dongbin Wang (Tehran University of Medical Sciences, 2021)
Background: The effects of transthyretin (TTR) over-expression on the proliferation and cell cycle of non-small cell lung cancer (NSCLC) A549 cells and its possible mechanism were verified. Methods: A total of 196 LC patients and 20 healthy controls were enrolled at Tianjin Hospital, Tianjin, China between Apr 2017 and Oct 2017. The serum TTR content was detected by ELISA. Through lentiviral transfection method, NSCLC cells were divided into non-transfected group (group A), negative control group (group B) transfected with empty vector and experimental group (group C) transfected with TTR over-expression. Cell proliferation was detected by CCK-8 method, TTR mRNA expression was detected by real-time quantitative polymerase chain reaction (RT-qPCR), and TTR protein expression was tested by Western blot (WB). Cell cycle was detected by flow cytometry, Wnt3a/β-catenin protein expression was detected by WB, and mRNA expression was detected by RT-qPCR. Results: The serum TTR content in early, middle and late LC group was remarkably lower than that in healthy group (P<0.05). Compared with late stage, TTR content in early and middle stages of LC group was higher, and the difference was statistically marked (P < 0.05). The absorbance value of group C was lower than that of groups A and B, indicating that the cell proliferation activity dramatically decreased, with statistically marked difference (P<0.05). LC A549 cells in group C were obviously blocked in G2M, with statistical significance (P<0.05).  Conclusion: TTR over-expression can inhibit the proliferation of NSCLC A549 cells, and the expression is related to Wnt3a/β-catenin pathway. TTR in serum of patients was helpful for diagnosing LC and has certain clinical value.